Análise e organização da cobertura aerofotogramétrica produzida pelo IBC/GERCA no Estado do Paraná no ano de 1970 - Oliveira, Wilson Francisco de (2012)
In the end of the 19th century and during long period of the 20th century, coffee economy played a fundamentally important role in the political, economic and social trajectories of Brazil. Such fact turns the historiographical research about the evolution of coffee national policy into an issue of high relevance for understanding fundamental issues of our recent history, be they environmental, social, political, economic, and cultural character, among others. From that perspective, the documental fund IBC/GERCA, which was produced by DACAF of Maringá under the custody of the Center Program of Historical Documentation of Maringá State University, is constituted of a historical repertoire which is essential for the study of regional history. It is necessary to consider the fact that such repertoire, until the present moment, has been rarely consulted by researchers interested in the matter, and yet, not once as primary source for specific projects on coffee growing, either by lack of a more discerning work or even by the lack adequate physical space for wide publicity and knowledge of it. This study aims the description and digitalization of the set of images "Aerial Photos", produced by IBC/GERCA in 1970, in the State of Paraná's Coffee Production Zone, under the jurisdiction of DACAF - Maringá, which is part of this documental fund.